A New Fe(III)/MOF‐5(Ni) Catalyst for Highly Selective Synthesis of Catechol from Phenol and Hydrogen Peroxide. Issue 4 (30th January 2019) - Xiang, Bai‐lin; Fu, Lin; Li, Yongfei; Liu, Yuejin
Abstract: A new Fe(III)/MOF‐5(Ni) catalyst with high hydrostability was prepared using an equal load method under room temperature, and nearly 100% selectivity for catechol and 63.2% yield of dihydroxybenzene were obtained in hydroxylation of phenol with H2 O2 over Fe(III)/MOF‐5(Ni) catalyst. Abstract : A new Fe(III)/MOF‐5(Ni) catalyst with high hydrostability was prepared using an equal load method under room temperature, and nearly 100% selectivity for catechol and 63.2% yield of dihydroxybenzene were obtained in hydroxylation of phenol with H2 O2 over Fe(III)/MOF‐5(Ni) catalyst.